2022
DOI: 10.1002/anie.202215866
|View full text |Cite
|
Sign up to set email alerts
|

A Low‐Concentration Electrolyte for High‐Voltage Lithium‐Metal Batteries: Fluorinated Solvation Shell and Low Salt Concentration Effect

Abstract: Concentration of electrolyte has significant effects on performances of rechargeable batteries. Previous studies mainly focused on concentrated electrolytes. So far, only several recipes on low-concentration electrolytes were studied, performing enhanced performance in advanced rechargeable batteries. Here, based on common electrolyte components, a lowconcentration electrolyte composed of 0.2 M lithium hexafluorophosphate (LiPF 6 ) solvated in fluoroethylene carbonate (FEC) and ethyl methyl carbonate (EMC) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 39 publications
(32 reference statements)
0
17
0
Order By: Relevance
“…Therefore, it is necessary to explore accurate characterization techniques of the interfacial solvated complex. (6) In the previous studies on the solvation complex, the effect of the electric double-layer (EDL) on the EEI film was often overlooked. The interactive structure existing at the inner Helmholtz layer describes the correlations between the electrolyte components and charged electrode surfaces.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is necessary to explore accurate characterization techniques of the interfacial solvated complex. (6) In the previous studies on the solvation complex, the effect of the electric double-layer (EDL) on the EEI film was often overlooked. The interactive structure existing at the inner Helmholtz layer describes the correlations between the electrolyte components and charged electrode surfaces.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…There are a growing number of studies that have shown that increasing the content of inorganic substances in the EEI film, such as LiF, Li 3 N, Li 2 S, Li 3 P, and Li 3 PO 4 , has an important positive significance in stabilizing the EEI film. [6][7][8][9] It is reported that the low Li + diffusion barrier of these inorganic components is conducive to regulating the uniform deposition of Li + , and the large band gap helps to prevent the tunneling effect of electrons and reduce the occurrence of interfacial side reactions. Therefore, a large number of electrolyte engineering approaches have focused on optimizing the electrolyte formulations and hope to build an EEI film that is rich in inorganic substances and has high Li + conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, constructing a dense and uniform SEI film can protect the Li metal from electrolyte attack and regulate the ion deposition direction. 140 Artificial SEI films not only improve interfacial stability and suppress volume changes, but also enhance surface lithophilicity and Li + flux redistribution. Moreover, it endows LMAs with uniform and dense electrode/electrolyte interfaces, which can redistribute Li + flux and tolerate lithium dendrite growth.…”
Section: Artificial Seimentioning
confidence: 99%
“…Traditional lithium-ion batteries (LIBs) are reaching their bottlenecks due to the theoretical capacity density limitations, which cannot meet the growing demands for electric vehicles and mobile power devices. [1][2][3][4] Lithium-sulfur batteries have been prioritized as the alternative for the development of next-generation highenergy energy-storage systems, attributed to the low cost, abundant supply, and environmental friendliness of sulfur, as well as its extremely high theoretical specific capacity of 1675 mAh g À1 and theoretical energy density of 2800 Wh kg À1 . [5][6][7][8][9][10] However, a series of issues remain to be solved, such as poor conductivity of sulfur materials, shuttle effect of dissolved lithium polysulfide, and structural destruction of the cathode material caused by volume changes during the cycle, which would result in dramatical capacity decay, low Coulomb efficiency, and poor rate performance of lithium-sulfur batteries.…”
Section: Introductionmentioning
confidence: 99%